„Życie na podsłuchu”. Ocena treści filmu w świetle praktyki działania Ministerstwa Bezpieczeństwa Państwowego NRD. Głos w dyskusji - Tytus Jaskułowski (Studia Filmoznawcze)
The article presents an analysis of the film The Lives of Others which assesses it accuracy in depicting the methods utilized by the Ministry of State Security of the GDR. It was undertaken in the context of the persistent post-2022 criticism of the production. My considerations are not limited to the historical plausibility of the main story arc, but also the depictions of the security officers’ professional ethics, their conduct, the jargon they use, and the equipment they were shown using. The analysis was supplemented with the results archival research on the functioning of the GDR as a state and more specifically — its security apparatus. The primary conclusion is that the depictions of the professional ethos and conduct of the officers was mostly accurate, at least as long as depicting these elements did not distort the coherence of the narrative. What is more, the main story arc is found to be reasonably plausible, as is the case with the vivid portrayal of the climate of fear and surveillance by the secret service, which was prevalent in the GDR.